2018
DOI: 10.1016/j.bbi.2017.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Protraction of neuropathic pain by morphine is mediated by spinal damage associated molecular patterns (DAMPs) in male rats

Abstract: We have recently reported that a short course of morphine, starting 10days after sciatic chronic constriction injury (CCI), prolonged the duration of mechanical allodynia for months after morphine ceased. Maintenance of this morphine-induced persistent sensitization was dependent on spinal NOD-like receptor protein 3 (NLRP3) inflammasomes-protein complexes that proteolytically activate interleukin-1β (IL-1β) via caspase-1. However, it is still unclear how NLRP3 inflammasome signaling is maintained long after m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 32 publications
(55 reference statements)
4
64
1
Order By: Relevance
“…In these two studies of morphine, only extracellular HMGB1, acting as a pro-inflammatory mediator, HMGB1 in the media also increased ( 66 , 67 ). Taken together, these findings indicate that morphine increases the expression and release of HMGB ( 66 , 67 ). Studies investigating the underlying mechanism demonstrated that TLR4, P2X7R, caspase-1 antagonists, and TLR4 siRNA inhibited the increased levels of HMGB1, while opioid receptor antagonists did not ( 66 ).…”
Section: Tlr4/opioid Receptor Pathway Crosstalkmentioning
confidence: 92%
See 1 more Smart Citation
“…In these two studies of morphine, only extracellular HMGB1, acting as a pro-inflammatory mediator, HMGB1 in the media also increased ( 66 , 67 ). Taken together, these findings indicate that morphine increases the expression and release of HMGB ( 66 , 67 ). Studies investigating the underlying mechanism demonstrated that TLR4, P2X7R, caspase-1 antagonists, and TLR4 siRNA inhibited the increased levels of HMGB1, while opioid receptor antagonists did not ( 66 ).…”
Section: Tlr4/opioid Receptor Pathway Crosstalkmentioning
confidence: 92%
“…In macrophages and monocytes, HMGB1 was found to be released after stimulation with LPS, TNF-α, or IL-1β ( 64 , 65 ). Notably, a study of chronic intrathecal injection of morphine showed that the expression of HMGB1, TLR4, and RAGE in the rat spinal dorsal horn increased ( 66 ), while another study of a neuropathic pain model showed that subcutaneous administration of morphine increased HMGB1 expression even at 5 weeks after morphine was ceased ( 67 ). In these two studies of morphine, only extracellular HMGB1, acting as a pro-inflammatory mediator, HMGB1 in the media also increased ( 66 , 67 ).…”
Section: Tlr4/opioid Receptor Pathway Crosstalkmentioning
confidence: 99%
“…After its activation by clozapine- N -oxide the morphine-induced persistent sensitization was prevented or enduringly reversed. It was further concluded that after peripheral nerve injury, morphine treatment results in persistent DAMP release via TLR4, P2X7R and caspase-1, which are involved in the formation/activation of NLRP3 inflammasomes [ 137 ].…”
Section: Chronic Painmentioning
confidence: 99%
“…The transcription factor NF-κB regulates the expression of inflammatory enzymes, such as COX-2 [3] and pro-inflammatory cytokines [4][5][6], which makes it one of the most important transcription factors during the inflammatory process and pain. Cytokines and chemokines released by these immune cells along with formyl-peptide (fMLP) released by dying cells activate vascular this paradoxical effect [25][26][27]. Corticosteroids and immunobiological agents are other group of molecules used to treat pain.…”
Section: Introductionmentioning
confidence: 99%